Plurality and the Poetics of Self - Bond, Bruce. author. aut Link
V, 123 p.
Keywords: Plurality and the Poetics of Self investigates the words “I” and “self” as suggestive of eight territories of meaning. Via poetry’s lens into language and its limits, Bruce Bond explores the notion of self as identity, volitional agent, ego, existential monad, subjectivity, ontological origin, soul, and transpersonal psyche. Taking poetic meaning as our common currency, the book emphasizes the critical role of the un-representable and how embattled and confused assumptions threaten ever deeper alienation from one another and ourselves.